Effect of Substitution of Spinach Flour (Amaranthus Sp) to Iron (Fe) Content and Acceptability of Donuts - Fathin Nabila (Journal of Nutraceuticals and Herbal Medicine, 2019)
Spinach is a great source of iron (Fe), which is quite high. Spinach can be made into spinach flour that can be used making donuts. Donuts in general have only macro nutrients and very few other nutrients, so substitution of spinach flour is needed to increase the nutritional content of donuts, especially on iron content. The purpose of this research is to know effect of substitution of spinach flour to iron content and acceptibility of donuts. The method this research used complete random design with four substitution treatment of spinach flour (0%, 10%, 20%, and 30%). Data analysis of iron content using one way ANOVA test with 95% significance level continued Duncan test, while acceptability using Kruskal Wallis test followed by Duncan test. The results showed that the highest iron content found in donuts with 30% spinach flour substitution with the result of 135.72 mg/kg, while the lowest on donuts with 0% spinach flour substitution with the result 43.78 mg/kg. Based on the overall percentage of acceptability the highest found in donuts with 0% spinach flour substitution, while the overall percentage of acceptability the lowest found in donuts with 30% spinach flour substitution. Based the analysis test known that there is effect of subtitution of spinach flour to iron content of donuts. There is also effect of substitution of spinach flour to acceptability color, aroma, flavor, texture, and overall donuts.